Assessing the Impact of Community Factors on Local Community Support for Tourism: An Empirical Investigation of the China-Pakistan-Economic Corridor - Shang, Yunfeng; Pitafi, Abdul Hameed; Rashid, Rao Muhammad (Frontiers in Psychology, 2022)
This research probes the influence of the construction of the China-Pakistan Economic Corridor (CPEC) on the pro-tourism development behavior of local residents. By applying social exchange theory (SET), this study examines the impact of the community dimension on pro-tourism development behavior through overall attitude. In addition, this study also examines the use of social media as a moderator in the relationship between overall attitude and pro-tourism development. A survey tool has been used to obtain data from the people of Gilgit-Baltistan. Hypotheses were examined using the structural equation method (SEM) on 417 survey responses. The findings indicated community satisfaction and an overall positive attitude to the effects of development, although a negative attitude regarding concerns about community resources. Overall, attitude has a significant impact on pro-tourism development behavior. Additionally, the use of social media strengthens the relationship between overall attitude and behavior that favors tourism development.